2001
DOI: 10.1007/s11837-001-0188-3
|View full text |Cite
|
Sign up to set email alerts
|

Recycling light metals from end-of-life vehicle

Abstract: The amount of aluminum used in cars and light trucks is growing steadily. However, without new developments in aluminum recycling technologies, sheet from automotive aluminum could eventually flood all current markets for recycled aluminum. This article summarizes the use of light metals and different alloys in transportation applications, the current auto recycling system, and new developments in the sorting of light metals by the metal recycling industry and by Huron Valley Steel Corporation, the world's lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…For example, aluminum with a high silicon and manganese content will turn the scrap gray while zinc and copper combine to turn the scrap dark [23]. However, color sorting cannot be used to separate individual alloys within a family.…”
Section: Color Sortingmentioning
confidence: 99%
“…For example, aluminum with a high silicon and manganese content will turn the scrap gray while zinc and copper combine to turn the scrap dark [23]. However, color sorting cannot be used to separate individual alloys within a family.…”
Section: Color Sortingmentioning
confidence: 99%
“…Thus far, the aluminum industry has been able to recycle a wide variety of alloys primarily by increasing the alloying element levels of the material to create foundry cast alloys, which have a higher tolerance for impurities but often require either additional alloying elements or the dilution of scrap with clean primary material to attain the necessary material qualities. 1,4,5 However, there are clear indications that blending and dilution are becoming less effective as the amount of the old scrap supply is increasing faster than demand for secondary casting applications that can absorb mixed scrap, resulting in a potential surplus of low-quality scrap. [6][7][8][9][10] To make use of all the aluminum scrap in the future and thus benefit from the potential energy and emission savings, it is therefore of utmost importance to identify alternative recycling strategies that are better suited to address the growing complexity of aluminum products.…”
Section: Introductionmentioning
confidence: 99%
“…The model used in that study allows for robust identification of the problem; however, its high aggregation level limits the evaluation of practical solutions because of the multitude of aluminum-containing components in automobiles and their highly complex alloys. Another group has developed a dynamic optimization model for end-of-life vehicles (ELV) recycling and demonstrated that product design by particle size reduction and liberation of material during shredding plays an important role in the composition and quality of recycling streams, 11,12 whereas others have investigated designs for recycling and optimization of refining and recycling processes, 1,2,13,14 Because automotive aluminum usage is expected to grow more rapidly in components consisting of wrought aluminum, 9,13,[15][16][17][18] it is important to identify components with wrought alloys or develop new ''recycling friendly'' alloys for these applications that could serve as intermediate reservoirs (sink alloys); such small-scale recycling practices have already begun. For example, Nissan collects and recycles aluminum wheels to construct suspension part and has developed pilot technology for bumper-to-bumper recycling.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, this wonderful methodology was also conducted to research other metals, such as copper [35][36][37][38][39][40], nickel [41], zinc [39,42,43], iron [26], lead [44,45], silver [46], phosphorus [47,48], and so on. In recent years, this method has been applied at a more micro level, and used to measure the recovery rate, recovery amount, and recovery potential of a certain kind of product within a region or a small area [49][50][51][52][53][54].…”
Section: Substance Flow Analysis (Sfa) and Brief Literature Reviewmentioning
confidence: 99%